Control Strategy Design for DC Motor Speed Regulation Using PID Controller - Dwi Santoso; Davut Izci (SEED: Journal of Scientific Research, 2026)
DC motor speed regulation remains a critical issue in industrial automation due to nonlinear dynamics, load disturbances, and parameter uncertainty. Proportional Integral Derivative control is still widely applied because of its simple structure and practical reliability. This study aims to design and evaluate an effective PID-based control strategy for DC motor speed regulation by integrating classical tuning and optimization-based approaches reported in recent literature. The research adopts a simulation-based experimental design using MATLAB/Simulink to model the DC motor and implement the PID controller. Performance indicators include rise time, settling time, overshoot, and steady-state error. The results show that optimally tuned PID controllers achieve stable speed regulation with low overshoot and fast transient response. Comparative analysis with previous studies confirms that hybrid and adaptive tuning methods significantly enhance robustness under varying load conditions. The findings indicate that PID control remains a competitive solution for DC motor speed regulation when supported by systematic tuning strategies. This study contributes a structured synthesis of recent PID-based control approaches and provides practical guidance for control system designers.